5.7.13 Problems 1201 to 1300

Table 5.587: Solved using series method

#

ODE

Mathematica

Maple

8147

\[ {}2 y^{\prime \prime }+x y^{\prime }+y = 0 \]

8148

\[ {}\left (x^{2}+4\right ) y^{\prime \prime }-y^{\prime }+y = 0 \]

8149

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

8150

\[ {}y^{\prime \prime }-\left (1+x \right ) y^{\prime }-x y = 0 \]

8151

\[ {}\left (x -1\right ) y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 0 \]

8152

\[ {}x^{2} \left (x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+\left (x +2\right ) y = 0 \]

8153

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (1+x \right ) y = 0 \]

8154

\[ {}x y^{\prime \prime }-4 y^{\prime }+x y = 0 \]

8155

\[ {}4 x^{2} y^{\prime \prime }+4 x^{2} y^{\prime }+2 y = 0 \]

8156

\[ {}2 x y^{\prime \prime }+\left (1-x \right ) y^{\prime }+y = 0 \]

8157

\[ {}x y^{\prime \prime }-\left (x -1\right ) y^{\prime }+2 y = 0 \]

8158

\[ {}x^{2} y^{\prime \prime }+x \left (1-x \right ) y^{\prime }+y = 0 \]

8159

\[ {}x y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 0 \]

8160

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+\left (x^{2}+x \right ) y^{\prime }+x y = 0 \]

8161

\[ {}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-3 x y^{\prime }+\left (x -1\right ) y = 0 \]

8162

\[ {}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }+\left (x^{2}+2 x \right ) y^{\prime }-x y = 0 \]

8163

\[ {}x^{3} y^{\prime \prime \prime }+\left (2 x^{3}-x^{2}\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

8164

\[ {}x^{3} y^{\prime \prime }+x^{2} y^{\prime }+y = 0 \]

8165

\[ {}9 \left (x -2\right )^{2} \left (x -3\right ) y^{\prime \prime }+6 x \left (x -2\right ) y^{\prime }+16 y = 0 \]

8166

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+p \left (p +1\right ) y = 0 \]

8212

\[ {}y^{\prime } = y^{2}-x \]

8214

\[ {}y^{\prime }-2 y = x^{2} \]

8216

\[ {}y^{\prime } = y+x \,{\mathrm e}^{y} \]

8218

\[ {}y^{\prime \prime }+y = 0 \]

8220

\[ {}y^{\prime \prime }-y = 0 \]

8222

\[ {}y^{\prime \prime }-y^{\prime } = 0 \]

8224

\[ {}y^{\prime \prime }+2 y^{\prime } = 0 \]

8226

\[ {}y^{\prime \prime }-x y = 0 \]

8227

\[ {}y^{\prime \prime }+x^{2} y = 0 \]

8228

\[ {}y^{\prime \prime }-2 x y^{\prime }+y = 0 \]

8229

\[ {}y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

8230

\[ {}y^{\prime \prime }+x^{2} y^{\prime }+x y = 0 \]

8231

\[ {}y^{\prime \prime }+2 x y^{\prime }+2 y = 0 \]

8232

\[ {}\left (x -1\right ) y^{\prime \prime }+y^{\prime } = 0 \]

8233

\[ {}\left (x +2\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

8234

\[ {}y^{\prime \prime }-\left (1+x \right ) y^{\prime }-y = 0 \]

8235

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-6 y = 0 \]

8236

\[ {}\left (x^{2}+2\right ) y^{\prime \prime }+3 x y^{\prime }-y = 0 \]

8237

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

8238

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

8239

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (2-x \right ) y^{\prime }+y = 0 \]

8240

\[ {}y^{\prime \prime }-2 x y^{\prime }+8 y = 0 \]

8241

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime } = 0 \]

8242

\[ {}y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8243

\[ {}y^{\prime \prime }+{\mathrm e}^{x} y^{\prime }-y = 0 \]

8244

\[ {}\cos \left (x \right ) y^{\prime \prime }+y^{\prime }+5 y = 0 \]

8245

\[ {}\cos \left (x \right ) y^{\prime \prime }+y^{\prime }+5 y = 0 \]

8246

\[ {}y^{\prime \prime }-x y = 1 \]

8247

\[ {}y^{\prime \prime }-4 x y^{\prime }-4 y = {\mathrm e}^{x} \]

8248

\[ {}x y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8249

\[ {}y^{\prime \prime }+5 x y^{\prime }+\sqrt {x}\, y = 0 \]

8250

\[ {}y^{\prime \prime }+x y^{\prime }+y = 0 \]

8251

\[ {}y^{\prime \prime }+y \cos \left (x \right ) = 0 \]

8252

\[ {}x^{3} y^{\prime \prime }+4 x^{2} y^{\prime }+3 y = 0 \]

8253

\[ {}x \left (x +3\right )^{2} y^{\prime \prime }-y = 0 \]

8254

\[ {}\left (x^{2}-9\right )^{2} y^{\prime \prime }+\left (x +3\right ) y^{\prime }+2 y = 0 \]

8255

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}+\frac {y}{\left (x -1\right )^{3}} = 0 \]

8256

\[ {}\left (x^{3}+4 x \right ) y^{\prime \prime }-2 x y^{\prime }+6 y = 0 \]

8257

\[ {}x^{2} \left (x -5\right )^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}-25\right ) y = 0 \]

8258

\[ {}\left (x^{2}+x -6\right ) y^{\prime \prime }+\left (x +3\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

8259

\[ {}x \left (x^{2}+1\right )^{2} y^{\prime \prime }+y = 0 \]

8260

\[ {}x^{3} \left (x^{2}-25\right ) \left (x -2\right )^{2} y^{\prime \prime }+3 x \left (x -2\right ) y^{\prime }+7 \left (5+x \right ) y = 0 \]

8261

\[ {}\left (x^{3}-2 x^{2}+3 x \right )^{2} y^{\prime \prime }+x \left (x -3\right )^{2} y^{\prime }-\left (1+x \right ) y = 0 \]

8262

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+5 \left (1+x \right ) y^{\prime }+\left (x^{2}-x \right ) y = 0 \]

8263

\[ {}x y^{\prime \prime }+\left (x +3\right ) y^{\prime }+7 x^{2} y = 0 \]

8264

\[ {}x^{2} y^{\prime \prime }+\left (\frac {5}{3} x +x^{2}\right ) y^{\prime }-\frac {y}{3} = 0 \]

8265

\[ {}x y^{\prime \prime }+y^{\prime }+10 y = 0 \]

8266

\[ {}2 x y^{\prime \prime }-y^{\prime }+2 y = 0 \]

8267

\[ {}2 x y^{\prime \prime }+5 y^{\prime }+x y = 0 \]

8268

\[ {}4 x y^{\prime \prime }+\frac {y^{\prime }}{2}+y = 0 \]

8269

\[ {}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

8270

\[ {}3 x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-y = 0 \]

8271

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {2}{9}\right ) y = 0 \]

8272

\[ {}2 x y^{\prime \prime }-\left (2 x +3\right ) y^{\prime }+y = 0 \]

8273

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {4}{9}\right ) y = 0 \]

8274

\[ {}9 x^{2} y^{\prime \prime }+9 x^{2} y^{\prime }+2 y = 0 \]

8275

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (2 x -1\right ) y = 0 \]

8276

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 0 \]

8277

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8278

\[ {}x y^{\prime \prime }-x y^{\prime }+y = 0 \]

8279

\[ {}y^{\prime \prime }+\frac {3 y^{\prime }}{x}-2 y = 0 \]

8280

\[ {}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }-y = 0 \]

8281

\[ {}x y^{\prime \prime }+y^{\prime }+y = 0 \]

8282

\[ {}x y^{\prime \prime }+\left (x -6\right ) y^{\prime }-3 y = 0 \]

8283

\[ {}x \left (x -1\right ) y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

8284

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{t}+\lambda y = 0 \]

8285

\[ {}x^{3} y^{\prime \prime }+y = 0 \]

8286

\[ {}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0 \]

8311

\[ {}2 x y^{\prime \prime }+y^{\prime }+y = 0 \]

8312

\[ {}y^{\prime \prime }-x y^{\prime }-y = 0 \]

8313

\[ {}\left (x -1\right ) y^{\prime \prime }+3 y = 0 \]

8314

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = 0 \]

8315

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

8316

\[ {}\cos \left (x \right ) y^{\prime \prime }+y = 0 \]

8317

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

8318

\[ {}\left (x +2\right ) y^{\prime \prime }+3 y = 0 \]

8319

\[ {}\left (1-2 \sin \left (x \right )\right ) y^{\prime \prime }+x y = 0 \]

8320

\[ {}y^{\prime \prime }+x y^{\prime }+y = 0 \]

8321

\[ {}x y^{\prime \prime }+\left (1-\cos \left (x \right )\right ) y^{\prime }+x^{2} y = 0 \]

8322

\[ {}\left ({\mathrm e}^{x}-1-x \right ) y^{\prime \prime }+x y = 0 \]